Aluminum profile machining process

CN122879786APending Publication Date: 2026-10-09贵州俊楷铝业科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611235799.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

六价铬虽然成膜致密、耐蚀性好,但属于强致癌物质,其使用和排放以受到严格限制

Benefits of technology

1. 脱脂无磷、中和无硝酸、钝化无铬、封孔无镍无氟,从源头消除重金属及富营养化污染物,显著降低废水处理成本和危废产生量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of aluminum profile processing, and discloses an aluminum profile processing technology, which is free of phosphorus, nitric acid, chromium, nickel and fluorine, and eliminates heavy metals and eutrophication pollutants from the source, thereby significantly reducing wastewater treatment cost and the amount of hazardous waste. The multiple synergistic protection of nano-SiO2 / rare earth composite anodic oxidation, chromium-free passivation and secondary oxidation synergistic film forming, and self-repairing nano-sealing hole significantly improves the corrosion resistance of the aluminum profile. Through the synergy of chromium-free passivation and secondary anodic oxidation, a double-layer gradient structure of a chemical conversion film and an electrochemical oxidation film is formed on the surface of the aluminum matrix, and the interlayer binding is firm, thereby fundamentally solving the problem of poor adhesion between the chromium-free passivation technology and the subsequent coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum profile processing technology, and more specifically to an aluminum profile processing technology. Background Technology

[0002] Aluminum and aluminum alloy profiles are widely used in construction, transportation, electronics and communications, and aerospace due to their advantages such as light weight, high specific strength, and good processing performance. To meet decorative and corrosion resistance requirements, the industry commonly performs surface treatment on aluminum profiles. A typical surface treatment process includes: degreasing → alkaline etching → neutralization → anodizing → sealing → electrophoretic coating or powder coating. Anodizing is the process of generating a porous anodic oxide film on the aluminum substrate surface through electrochemical methods in a sulfuric acid electrolyte. Sealing involves sealing the micropores of the oxide film using physical or chemical methods to reduce film adhesion and improve corrosion resistance and electrical insulation.

[0003] In the passivation process, existing technologies mostly employ chromate passivation processes with hexavalent chromium as the main component. Although hexavalent chromium forms a dense film and has good corrosion resistance, it is a potent carcinogen, and its use and emissions are strictly restricted. With "environmental protection" becoming a key objective for various industries, the green transformation of the aluminum profile surface treatment industry has become an inevitable trend.

[0004] However, existing aluminum profile surface treatment processes still have the following shortcomings in terms of environmental protection and overall performance: (I) Heavy metal pollution in the passivation process. Traditional aluminum profile surface treatment typically employs chromate passivation, a simple, low-cost process with good corrosion resistance. However, hexavalent chromium ions in the passivation film are serious carcinogens, posing a significant threat to human health and the ecological environment. Although some studies have attempted to replace chromates with zirconium / titanium salt systems, existing chromium-free passivation technologies generally suffer from insufficient corrosion resistance of the passivation film and poor adhesion to subsequent coatings.

[0005] (II) Problems of Harmful Element Residue in the Sealing Process. Existing sealing processes are mainly divided into three categories: low-temperature sealing, medium-temperature sealing, and high-temperature sealing. While high-temperature boiling water sealing does not use toxic chemicals, it requires maintaining the temperature close to 100℃, resulting in extremely high energy consumption. Existing technologies use sealing baths containing nickel fluoride and chromium fluoride for aluminum alloy anodized profiles, but heavy metal pollution is still unavoidable. In recent years, research has emerged on nickel-free sealing agents, such as sealing methods using rare earth nitrates and lithium salts as the main salts. However, these methods involve high sealing temperatures and long sealing times, resulting in low efficiency and excessive energy consumption. Other nickel-free sealing agents use raw materials such as sodium silicate, but after sealing, the workpiece surface is prone to whitening, powdering, and loss of gloss.

[0006] (III) Technical limitations of the anodizing process. Conventional sulfuric acid anodizing films enhance protective capabilities, but the oxide films contain a large number of micropores, making it difficult to achieve high corrosion resistance.

[0007] (iv) Pollutant discharge issues. The use of phosphates and nitric acids in traditional degreasing and neutralization processes results in wastewater containing large amounts of phosphorus and nitrates, causing eutrophication pollution of water bodies. Although appropriate treatment is carried out before discharge, a green process solution covering the entire process has not yet been formed.

[0008] In summary, existing aluminum profile surface treatment processes present the following technical contradictions: traditional chromium-, nickel-, and fluorine-containing processes can meet corrosion resistance requirements, but they suffer from serious heavy metal and harmful element pollution; while chromium- and nickel-free alternatives achieve environmental protection goals, they generally suffer from insufficient corrosion resistance, low sealing efficiency, high energy consumption, or poor process stability. Currently, there is a lack of an aluminum profile surface treatment process that can simultaneously achieve both overall green environmental protection and excellent comprehensive performance. Summary of the Invention

[0009] The present invention aims to provide an aluminum profile processing technology that addresses the shortcomings of existing aluminum profile surface treatment processes.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: an aluminum profile processing technology, comprising the following steps: S1. Degreasing: The aluminum profile is immersed in a degreasing agent for degreasing treatment, wherein the degreasing agent contains a nonionic surfactant, fatty alcohol polyoxyethylene ether, sodium gluconate and deionized water; S2. Alkaline etching: The degreased aluminum profile is immersed in an alkaline etching solution for alkaline etching treatment; S3. Neutralization: The aluminum profiles after alkaline etching are neutralized and de-ashed using a neutralization solution prepared from a mixture of dilute sulfuric acid and hydrogen peroxide; S4. Primary anodizing: The neutralized aluminum profile is placed in a sulfuric acid electrolyte for anodizing treatment, wherein the sulfuric acid electrolyte contains nano-SiO2 and rare earth cerium salt; S5. Chromium-free passivation: The aluminum profile after one anodizing is immersed in a passivation solution for passivation treatment, wherein the passivation solution contains 1.5~3 g / L fluorozirconic acid, 0.5~2 g / L silane coupling agent, and 0.3~1 g / L cerium nitrate; S6. Secondary anodizing: The chromium-free passivated aluminum profile is placed in a sulfuric acid electrolyte for secondary anodizing treatment. The sulfuric acid concentration is 80~120g / L. A thin oxide layer with nanoscale pores is formed on the surface of the passivation film and oxide film. S7. Nanocomposite sealing: The aluminum profile after secondary anodizing is immersed in a sealing agent of polycarboxylic acid organic salt system for sealing treatment. The sealing agent contains nano-containers loaded with corrosion inhibitors. The nano-containers are embedded in the micropores of the oxide film during the sealing process to form a composite sealing layer with corrosion response and self-healing function. S8. Coating: Apply electrophoretic coating or powder coating to the sealed aluminum profiles.

[0011] Preferably, as an improvement, in step S1, the degreasing temperature is 45~55℃ and the degreasing time is 5~8 minutes.

[0012] Preferably, as an improvement, in step S4, the sulfuric acid concentration in the sulfuric acid electrolyte is 150~180 g / L, the nano-SiO2 content is 1~3 g / L, and the rare earth cerium salt content is 0.5~1.5 g / L; Preferably, as an improvement, in step S4, the anodizing temperature is 15~25℃ and the current density is 1.2~2 A / dm³. 2 The oxidation time is 25-40 minutes, and the thickness of the anodic oxide film is 15-25 μm.

[0013] Preferably, as an improvement, in step S5, the passivation temperature is 20~30℃ and the passivation time is 1~3 minutes.

[0014] Preferably, as an improvement, in step S6, the current density for secondary anodizing is 0.5~0.8 A / dm³. 2 The temperature is 15~20℃, and the time is 5~10 minutes.

[0015] Preferably, as an improvement, in step S7, the sealing agent comprises, by weight parts: 12-14 parts of polycarboxylate organic salt, 4-5 parts of sodium molybdate corrosion inhibitor, 6-8 parts of organic acid, 8-10 parts of polyvinyl alcohol, 10-12 parts of polymer dispersant, 4.5-6 parts of surfactant, 5-6 parts of complexing agent, and 48-50 parts of deionized water; the sealing temperature is 55-60°C, and the sealing time is 15-25 minutes.

[0016] Preferably, as an improvement, in step S7, the nanocontainer loaded with corrosion inhibitor is a mesoporous SiO2 nanoparticle loaded with molybdate corrosion inhibitor; when microcracks appear in the composite sealing layer, the nanocontainer releases the corrosion inhibitor to repair the damaged area.

[0017] Preferably, as an improvement, in step S8, the electrophoretic coating uses fluorosilicone modified acrylic resin electrophoretic paint, the electrophoresis voltage is 80~120V, the electrophoresis time is 2~3 minutes, the curing temperature is 170~180℃, and the curing time is 20~25 minutes.

[0018] The beneficial technical effects of this solution are: 1. Degreasing is phosphorus-free, neutralization is nitric acid-free, passivation is chromium-free, and sealing is nickel-free and fluorine-free, eliminating heavy metals and eutrophic pollutants at the source, significantly reducing wastewater treatment costs and hazardous waste generation.

[0019] 2. The use of medium-temperature sealing instead of high-temperature boiling water sealing significantly reduces heating energy consumption and is a typical green and low-carbon process; at the same time, the sealing time is significantly shortened, and production efficiency is significantly improved.

[0020] 3. Through the synergistic protective effects of nano-SiO2 / rare earth composite anodizing, chromium-free passivation and secondary oxidation film formation, and self-healing nano-sealing, the corrosion resistance of aluminum profiles is significantly improved, surpassing the level of traditional chromium-containing passivation and nickel-containing sealing processes.

[0021] 4. The nano-container embedded in the sealing layer with corrosion inhibitor gives the coating a corrosion-response self-healing ability—when micro-cracks appear in the coating, it can automatically release the corrosion inhibitor to repair the damaged area, effectively extending the service life of aluminum profiles in harsh environments.

[0022] 5. High-quality sealing and excellent appearance. The sealing process is dense and efficient, and the surface of the profile is free from defects such as whitening, powdering, and loss of gloss after sealing. The gloss is well maintained, meeting the surface quality requirements of high-end decorative aluminum profiles.

[0023] 6. Strong adhesion between layers and good process stability. Through the synergy of chromium-free passivation and secondary anodizing, a double-layer gradient structure of chemical conversion film and electrochemical oxide film is formed on the surface of aluminum substrate. The interlayer adhesion is strong, fundamentally solving the problem of poor adhesion to subsequent coatings that is common in existing chromium-free passivation technologies. Detailed Implementation

[0024] The following detailed description illustrates the specific implementation method: Example 1: An aluminum profile processing technology, comprising the following steps: S1. Degreasing: The aluminum profile is immersed in a degreasing agent for degreasing treatment at a temperature of 45°C for 8 minutes. The degreasing agent contains a nonionic surfactant, fatty alcohol polyoxyethylene ether, sodium gluconate, and deionized water; that is, the degreasing agent is phosphorus-free and nitrogen-free. S2. Alkaline etching: The degreased aluminum profile is immersed in an alkaline etching solution for alkaline etching treatment; S3. Neutralization: The aluminum profiles after alkaline etching are neutralized and de-ashed using a neutralization solution prepared from a mixture of dilute sulfuric acid and hydrogen peroxide; S4. Primary Anodizing: The neutralized aluminum profile is placed in a sulfuric acid electrolyte for anodizing treatment. The sulfuric acid electrolyte contains nano-SiO2 and rare earth cerium salts; the sulfuric acid concentration in the electrolyte is 180 g / L, the nano-SiO2 content is 1 g / L, and the rare earth cerium salt content is 0.5 g / L; the anodizing temperature is 15℃, and the current density is 1.6 A / dm³. 2 The oxidation time was 25 minutes, and the thickness of the anodic oxide film was 15 μm.

[0025] S5. Chromium-free passivation: The aluminum profile after one anodizing is immersed in a passivation solution for passivation treatment at a temperature of 25°C for 1-3 minutes. The passivation solution contains 2.5 g / L fluorozirconic acid, 1.5 g / L silane coupling agent, and 1 g / L cerium nitrate. S6. Secondary Anodizing: The chromium-free passivated aluminum profile is placed in a sulfuric acid electrolyte for secondary anodizing treatment. The sulfuric acid concentration is 80 g / L. A thin oxide layer with nanoscale pores is formed on the surface of the already formed passivation film and oxide film; the current density is 0.5 A / dm³. 2 The temperature was 18℃, and the time was 10 minutes. S7. Nanocomposite Sealing: The aluminum profile after secondary anodizing is immersed in a sealing agent based on a polycarboxylic acid organic salt system for sealing treatment. The sealing temperature is 60°C and the sealing time is 15 minutes. The sealing agent contains nano-containers loaded with corrosion inhibitors. During the sealing process, the nano-containers are embedded in the micropores of the oxide film to form a composite sealing layer with corrosion-responsive self-healing function. The sealing agent contains, by weight, 14 parts of polycarboxylic acid organic salt, 5 parts of sodium molybdate corrosion inhibitor, 6 parts of organic acid, 8 parts of polyvinyl alcohol, 10 parts of polymer dispersant, 6 parts of surfactant, 5 parts of complexing agent, and 50 parts of deionized water. S8. Coating: The sealed aluminum profiles are then coated with electrophoretic paint using fluorosilicone modified acrylic resin. The electrophoresis voltage is 80V, the electrophoresis time is 2 minutes, the curing temperature is 180℃, and the curing time is 20 minutes. Powder coating can also be used.

[0026] Example 2: An aluminum profile processing technology, comprising the following steps: S1. Degreasing: The aluminum profile is immersed in a degreasing agent for degreasing treatment at a temperature of 55°C for 5 minutes. The degreasing agent contains a nonionic surfactant, fatty alcohol polyoxyethylene ether, sodium gluconate, and deionized water; that is, the degreasing agent is phosphorus-free and nitrogen-free. S2. Alkaline etching: The degreased aluminum profile is immersed in an alkaline etching solution for alkaline etching treatment; S3. Neutralization: The aluminum profiles after alkaline etching are neutralized and de-ashed using a neutralization solution prepared from a mixture of dilute sulfuric acid and hydrogen peroxide; S4. Primary Anodizing: The neutralized aluminum profile is placed in a sulfuric acid electrolyte for anodizing treatment. The sulfuric acid electrolyte contains nano-SiO2 and rare earth cerium salts; the sulfuric acid concentration in the electrolyte is 150 g / L, the nano-SiO2 content is 3 g / L, and the rare earth cerium salt content is 1 g / L; the anodizing temperature is 25℃, and the current density is 1.2 A / dm³. 2 The oxidation time was 30 minutes, and the thickness of the anodic oxide film was 20 μm.

[0027] S5. Chromium-free passivation: The aluminum profile after one anodizing is immersed in a passivation solution for passivation treatment at a temperature of 30°C for 1-3 minutes. The passivation solution contains 1.5 g / L fluorozirconic acid, 2 g / L silane coupling agent, and 0.3 g / L cerium nitrate. S6. Secondary Anodizing: The chromium-free passivated aluminum profile is placed in a sulfuric acid electrolyte for secondary anodizing treatment. The sulfuric acid concentration is 100 g / L. A thin oxide layer with nanoscale pores is formed on the surface of the already formed passivation film and oxide film; the current density is 0.8 A / dm³. 2 The temperature was 20℃, and the time was 5 minutes. S7. Nanocomposite Sealing: The aluminum profile after secondary anodizing is immersed in a sealing agent based on a polycarboxylic acid organic salt system for sealing treatment. The sealing temperature is 55°C and the sealing time is 25 minutes. The sealing agent contains nano-containers loaded with corrosion inhibitors. During the sealing process, the nano-containers are embedded in the micropores of the oxide film to form a composite sealing layer with corrosion-responsive self-healing function. The sealing agent contains, by weight, 12 parts of polycarboxylic acid organic salt, 5 parts of sodium molybdate corrosion inhibitor, 7 parts of organic acid, 10 parts of polyvinyl alcohol, 10 parts of polymer dispersant, 5 parts of surfactant, 6 parts of complexing agent, and 48 parts of deionized water. S8. Coating: The sealed aluminum profiles are then coated with electrophoretic paint using fluorosilicone modified acrylic resin. The electrophoretic voltage is 100V, the electrophoresis time is 2 minutes, the curing temperature is 170℃, and the curing time is 25 minutes. Powder coating can also be used.

[0028] Example 3: An aluminum profile processing technology, comprising the following steps: S1. Degreasing: The aluminum profile is immersed in a degreasing agent for degreasing treatment at a temperature of 50°C for 5 minutes. The degreasing agent contains a nonionic surfactant, fatty alcohol polyoxyethylene ether, sodium gluconate, and deionized water; that is, the degreasing agent is phosphorus-free and nitrogen-free. S2. Alkaline etching: The degreased aluminum profile is immersed in an alkaline etching solution for alkaline etching treatment; S3. Neutralization: The aluminum profiles after alkaline etching are neutralized and de-ashed using a neutralization solution prepared from a mixture of dilute sulfuric acid and hydrogen peroxide; S4. Primary Anodizing: The neutralized aluminum profile is placed in a sulfuric acid electrolyte for anodizing treatment. The sulfuric acid electrolyte contains nano-SiO2 and rare earth cerium salts. The sulfuric acid concentration in the electrolyte is 165 g / L, the nano-SiO2 content is 3 g / L, and the rare earth cerium salt content is 1.5 g / L. The anodizing temperature is 20℃, and the current density is 2 A / dm³. 2 The oxidation time was 40 minutes, and the thickness of the anodic oxide film was 25 μm.

[0029] S5. Chromium-free passivation: The aluminum profile after one anodizing is immersed in a passivation solution for passivation treatment at a temperature of 25°C for 1-3 minutes. The passivation solution contains 3 g / L fluorozirconic acid, 0.5 g / L silane coupling agent, and 1 g / L cerium nitrate. S6. Secondary Anodizing: The chromium-free passivated aluminum profile is placed in a sulfuric acid electrolyte for secondary anodizing treatment. The sulfuric acid concentration is 120 g / L. A thin oxide layer with nanoscale pores is formed on the surface of the already formed passivation film and oxide film; the current density is 0.8 A / dm³. 2 The temperature was 15℃, and the time was 8 minutes. S7. Nanocomposite Sealing: The aluminum profile after secondary anodizing is immersed in a sealing agent based on a polycarboxylic acid organic salt system for sealing treatment. The sealing temperature is 60°C and the sealing time is 15 minutes. The sealing agent contains nano-containers loaded with corrosion inhibitors. The nano-containers are embedded in the micropores of the oxide film during the sealing process to form a composite sealing layer with corrosion-responsive self-healing function. The sealing agent contains, by mass parts: 14 parts polycarboxylic acid organic salt, 4 parts sodium molybdate corrosion inhibitor, 8 parts organic acid, 8 parts polyvinyl alcohol, 12 parts polymer dispersant, 4.5 parts surfactant, 5 parts complexing agent, and 48 parts deionized water. S8. Coating: The sealed aluminum profiles are then coated with electrophoretic paint using fluorosilicone modified acrylic resin. The electrophoresis voltage is 120V, the electrophoresis time is 3 minutes, the curing temperature is 175℃, and the curing time is 25 minutes. Powder coating can also be used.

[0030] The gloss retention rate of the samples after sealing in Examples 1-3 was measured at 60° specular gloss, and the results are as follows:

[0031] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. Aluminum profile processing technology, characterized in that, Includes the following steps: S1. Degreasing: The aluminum profile is immersed in a degreasing agent for degreasing treatment, wherein the degreasing agent contains a nonionic surfactant, fatty alcohol polyoxyethylene ether, sodium gluconate and deionized water; S2. Alkaline etching: The degreased aluminum profile is immersed in an alkaline etching solution for alkaline etching treatment; S3. Neutralization: The aluminum profiles after alkaline etching are neutralized and de-ashed using a neutralization solution prepared from a mixture of dilute sulfuric acid and hydrogen peroxide; S4. Primary anodizing: The neutralized aluminum profile is placed in a sulfuric acid electrolyte for anodizing treatment, wherein the sulfuric acid electrolyte contains nano-SiO2 and rare earth cerium salt; S5. Chromium-free passivation: The aluminum profile after one anodizing is immersed in a passivation solution for passivation treatment, wherein the passivation solution contains 1.5~3 g / L fluorozirconic acid, 0.5~2 g / L silane coupling agent, and 0.3~1 g / L cerium nitrate; S6. Secondary anodizing: The chromium-free passivated aluminum profile is placed in a sulfuric acid electrolyte for secondary anodizing treatment. The sulfuric acid concentration is 80~120g / L. A thin oxide layer with nanoscale pores is formed on the surface of the passivation film and oxide film. S7. Nanocomposite sealing: The aluminum profile after secondary anodizing is immersed in a sealing agent of polycarboxylic acid organic salt system for sealing treatment. The sealing agent contains nano-containers loaded with corrosion inhibitors. The nano-containers are embedded in the micropores of the oxide film during the sealing process to form a composite sealing layer with corrosion response and self-healing function. S8. Coating: Apply electrophoretic coating or powder coating to the sealed aluminum profiles.

2. The aluminum profile processing technology according to claim 1, characterized in that, In step S1, the degreasing temperature is 45~55℃ and the degreasing time is 5~8 minutes.

3. The aluminum profile processing technology according to claim 1, characterized in that, In step S4, the sulfuric acid concentration in the sulfuric acid electrolyte is 150~180 g / L, the nano-SiO2 content is 1~3 g / L, and the rare earth cerium salt content is 0.5~1.5 g / L.

4. The aluminum profile processing technology according to claim 1, characterized in that, In step S4, the anodizing temperature is 15~25℃, and the current density is 1.2~2 A / dm³. 2 The oxidation time is 25-40 minutes, and the thickness of the anodic oxide film is 15-25 μm.

5. The aluminum profile processing technology according to claim 1, characterized in that, In step S5, the passivation temperature is 20~30℃ and the passivation time is 1~3 minutes.

6. The aluminum profile processing technology according to claim 1, characterized in that, In step S6, the current density for secondary anodizing is 0.5~0.8 A / dm³. 2 The temperature is 15~20℃, and the time is 5~10 minutes.

7. The aluminum profile processing technology according to claim 1, characterized in that, In step S7, the sealing agent comprises, by mass parts: 12-14 parts of polycarboxylate organic salt, 4-5 parts of sodium molybdate corrosion inhibitor, 6-8 parts of organic acid, 8-10 parts of polyvinyl alcohol, 10-12 parts of polymer dispersant, 4.5-6 parts of surfactant, 5-6 parts of complexing agent, and 48-50 parts of deionized water; the sealing temperature is 55-60°C, and the sealing time is 15-25 minutes.

8. The aluminum profile processing technology according to claim 7, characterized in that, In step S7, the nanocontainer loaded with corrosion inhibitor is a mesoporous SiO2 nanoparticle loaded with molybdate corrosion inhibitor; when microcracks appear in the composite sealing layer, the nanocontainer releases the corrosion inhibitor to repair the damaged area.

9. The aluminum profile processing technology according to claim 1, characterized in that, In step S8, the electrophoretic coating uses fluorosilicone modified acrylic resin electrophoretic paint, the electrophoresis voltage is 80~120V, the electrophoresis time is 2~3 minutes, the curing temperature is 170~180℃, and the curing time is 20~25 minutes.